2022
DOI: 10.1007/s11606-022-07674-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Standardized Hospitalist Information Cards on the Patient Experience: a Quasi-Experimental Prospective Cohort Study

Abstract: Background Communication with clinicians is an important component of a hospitalized patient’s experience. Objective To test the impact of standardized hospitalist information cards on the patient experience. Design Quasi-experimental study in a U.S. tertiary-care center. Participants All-comer medicine inpatients. Interventions Standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Studies have shown improvement in physician recognition with the use of business/informational cards. 22 Physicians who distributed cards also were perceived to be better communicators 23,24 and provide higher quality care. 23 Handing out these cards can be an easily replicable and low-cost solution to improve recognition, communication, and perceived quality of care.…”
Section: Provide Informational Cardsmentioning
confidence: 99%
“…Studies have shown improvement in physician recognition with the use of business/informational cards. 22 Physicians who distributed cards also were perceived to be better communicators 23,24 and provide higher quality care. 23 Handing out these cards can be an easily replicable and low-cost solution to improve recognition, communication, and perceived quality of care.…”
Section: Provide Informational Cardsmentioning
confidence: 99%